Enhanced process monitoring, control & reviewing system - Philip, Regi. (2009)
This thesis describes the development, design and implementation of an enhanced Process Monitoring, Control and Reviewing System which helps to eliminate human factors in input controlled, high precision, high value, high speed, long cycle time, mass production processes like semiconductor wafer processing. The design of this system is based on the requirement for a hundred percent on-line monitoring for the semiconductor wafer processing specifically in the Plasma etching process. The need for such a system was increasingly feit during the years of working in this field since any process errors accounted to great losses due to the long cycle time and complicated process steps involved in wafer fabrication process. Though this system was developed for the above it can be can be easily adapted to other similar processes like those in pharmaceutical and petroleum industries. The designed system which is named as the Intelligent Digital Data Recording (IDDR) system is a hybrid system that combines software and hardware to achieve the desired objective. The system is designed with significant level of intelligence to make appropriate decisions and exercise control over the process it monitors. This system runs in Borland C++ under the window environment which makes it very user-friendly and compatible with existing systems widely used in the industrial context. This system was successfully tested on a plasma etching process in a local wafer fabrication plant.